Efficient spin injection and giant magnetoresistance in Fe/MoS2/Fe junctions - SANVITO, STEFANO; NARAYAN, AWADHESH; RUNGGER, IVAN (My University, 2014)
We demonstrate giant magnetoresistance in Fe/MoS2/Fe junctions by means of ab initio transport calculations. We show that junctions incorporating either a monolayer or a bilayer of MoS2 are metallic and that Fe acts as an efficient spin injector into MoS2 with an efficiency of about 45%. This is the result of the strong coupling between the Fe and S atoms at the interface. For junctions of greater thickness, a maximum magnetoresistance of ∼300% is obtained, which remains robust with the applied bias as long as transport is in the tunneling limit. A general recipe for improving the magnetoresistance in spin valves incorporating layered transition metal dichalcogenides is proposed.
PUBLISHED
Keywords: giant magnetoresistance; Nanoscience & Materials